EXAMINING THE IMPACT OF TRANSFORMATIONAL LEADERSHIP, COMPETENCE, AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT THE BANDAR LAMPUNG MIDDLE TAX SERVICE OFFICE - Anggraito, Risetia; Wahyudi, Agus; Barusman, Yusuf Sulfarano (Program Studi Magister Manajemen, 2024)
Currently, tax revenue is the backbone of revenue in the State Budget. The Directorate General of Taxes continues to improve its performance so that tax revenue targets are achieved by trying to improve its performance through tax administration and bureaucratic reform programs. Tax administration and bureaucratic reform cannot be separated from the role of transformational leadership. In addition to the application of the right leadership style, there are internal factors that influence employee performance, namely competence and work motivation. This study aimed to examine the effects of transformational leadership, competence, and work motivation on employee performance, both individually and collectively. Using a quantitative approach, data was collected through questionnaires and supported by secondary sources. Multiple linear regression analysis with SPSS 27 was used for data analysis. A sample of 95 employees from KPP Madya Bandar Lampung was selected using simple random sampling. The results showed that transformational leadership, competence, and work motivation significantly influence employee performance, accounting for 67.3% of the variation, while the remaining 32.7% is due to other factors not included in the study.